PERAN PEMEDIASIAN KOMITMEN ORGANISASI PADA PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP INTENTION TO LEAVE - Puspita Dewi, Made; Ganesha Rahyuda, Agoes (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
The aim of this study is to determine the mediating role of organizational commitment on the influence of perceived organizational support on intention to leave of the employees of Discovery Kartika Plaza Hotel. The number of samples is 195 employees by using probability sampling method especially techniques of analysis used are Path analysis and Sobel test. The results show that perceived organizational support and organizational commitment negatively affect intention to leave, perceived organizational support positively influence organizational commitment and organizational commitment mediates on intention to leave. It is recommended for the company for continuing perceived organizational support to employees and high commitment, and the management should be able to be a good co-worker for the employees so that employees desire not to leave the company can be reduced.
Keywords: perceived organizational support; komitmen organisasi; intention to leave